Privación sensorial - Ardila, Rubén (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
Experimental research on sensory deprivation began in 1954 at McGill University in Montreal, Canada, under the inspiration of the Chinese “brain-washing.” The procedures include dark rooms with different degrees of environmental isolation and tanks filled with water in which the subject is placed. Sensory deprivation has been found to have effects on perception, cognition, learning, and motor reactions. Several theories have been proposed to explain the experimental findings. The importance of this area for the understanding of human perceptual behavior is stressed.